14 Does rehabilitation after traumatic brain injury have to be so complicated?. Issue 3 (15th February 2011) - Allanson, J; Seeley, H M; Psaila, K; Bateman, A; Gardner, A; Pickar, J D; Hutchinson, P J
Abstract : Historical benchmarking to determine the rehabilitation pathways of Neurotrauma clinic attendees in a PCT where there is no community head injury service. Although national guidelines recommend neurological rehabilitation after head injury, acquiring funding for new services still demands evidence of effectiveness. Therefore, before developing a new service we performed an historical benchmarking exercise to understand current service provision. Over 2 years, 86 adults (70% of admissions with intracranial injury and 5% of all admissions with head injury from our PCT) had been admitted to regional neurosurgical beds and 30 of these then referred to the neuro-trauma clinic. Using the clinic data base, 46 PCT residents injured between 1.1.07 and 12.31.08 were identified. 35 % of those seen had not been inpatients but were referred with problems up to 3 years after injury. After notes review and a semi-structured interview their rehabilitation pathway was documented using previously published rehabilitation codes. Only 4 of the 30 admitted had a documented rehabilitation plan on discharge. Patients had accessed up to 6 services each. Five had been assessed in considerable detail meeting up to six psychologists within 2 years. Intensive daily neuropsychological rehabilitation had been received by 3 of 14 referred from clinic, starting between 18 and 30 months after injury. Conclusion: Excellent specialised services exist but access was very limited and often significantly delayed. Solutions will be discussed.